PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA DI KOPERASI SIMPAN PINJAM â€œAPINGâ€™ KECAMATAN ASEMBAGUS SITUBONDO DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Lestari, Indah Nita; Wahyuni, Ika; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The cooperatives are organizations that carry out economic activities within a specific framework, guided by shared principles and ideals. The Cooperatives have a responsibility to their members to run their operations efficiently and competitively. Associate members and the more comprehensive community benefit from the cooperativesâ€™ efforts to improve their financial status because of their essential economic role. To meet the needs of its members as a whole, the cooperatives are engaged in trade and other activities. Cooperatives play an essential role in developing joint ventures with people who have weak economic means. The purpose of this study was to analyze and test the effect of Leadership, Work Discipline and Work Environment on Performance at â€œAPINGâ€ Saving and Loan Cooperative in Asembagus Situbondo District with Work Motivation as an Intervening Variableâ€. This research is quantitative. The population used in this study were 40 employees of the Asembagus â€œAPINGâ€ Savings and Loan Cooperative. The sampling technique used was saturated sampling. This studyâ€™s data analysis and hypothesis testing used the Structural Equation Method - Partial Least Square (PLS-SEM). The direct effect hypothesis test results using the Smart PLS 3.0 application show that Leadership, Work discipline and work environment affect work motivation and performance at the â€œAPINGâ€ Savings and Loan Cooperative in Asembagus. The indirect effect hypothesis test results show that leadership on performance through work motivation has no significant positive effect. In contrast, work discipline and work environment affect performance through work motivation and have a significant positive effect.